2017
DOI: 10.1002/cncr.30801
|View full text |Cite
|
Sign up to set email alerts
|

Association between patients' perception of the comorbidity burden and symptoms in outpatients with common solid tumors

Abstract: Background Cancer patients’ symptom burden is commonly attributed to their cancer and its treatment. Increasingly, cancer patients have many other chronic comorbid conditions. However the degree to which these comorbid conditions may contribute to patient-reported symptom burden is unclear. Methods We explored the relationship between the presence of comorbid conditions, symptom experience and burden, and perceived bother from cancer or comorbid conditions in 3106 cancer patients. We examined the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
5
11
3
1
Order By: Relevance
“…Although multimorbidity was associated with higher symptom burden, cancer was not. Severe and persistent symptoms have previously been linked to multimorbidity in community‐dwelling older adults, and greater symptom burden has been associated with multimorbidity in individuals with cancer . These findings, in concert with those of previous studies, suggest that, in many instances, noncancer diagnoses drive symptom burden whether the individual has cancer or not.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Although multimorbidity was associated with higher symptom burden, cancer was not. Severe and persistent symptoms have previously been linked to multimorbidity in community‐dwelling older adults, and greater symptom burden has been associated with multimorbidity in individuals with cancer . These findings, in concert with those of previous studies, suggest that, in many instances, noncancer diagnoses drive symptom burden whether the individual has cancer or not.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies suggest that individuals with life‐limiting illness have high symptom burden, particularly pain, regardless of diagnosis . Multimorbidity is also common in individuals with cancer, and clinicians have difficultly addressing these individuals’ symptoms . Providers of cancer care may not consider that symptoms might be emanating from conditions other than cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has suggested that lower functional status and/or a higher level of comorbidity are associated with a higher symptom burden . However, in the current study, the relative contribution of lower functional status and higher comorbidity to a survivor's symptom burden was much smaller than the effects of stress (ie, 3.0% and 0.9%, respectively).…”
Section: Discussioncontrasting
confidence: 79%
“…A growing body of evidence has suggested that lower functional status and/or a higher level of comorbidity are associated with a higher symptom burden. 33,[46][47][48] However, in the current study, the relative contribution of lower functional status and higher comorbidity to a survivor's symptom burden was much smaller than the effects of stress (ie, 3.0% and 0.9%, respectively). Given the cross-sectional nature of the current study, additional research is warranted to evaluate the longitudinal relationships between changes in symptom burden, levels of comorbidity, and functional status among cancer survivors.…”
Section: Discussioncontrasting
confidence: 70%
“…Clinical variables such as these appear to impact medication adherence and response to therapy differently from physician adherence/adherence to medical visits. The findings of the current study align with the belief that clinical variables such as the number of comorbid conditions, obesity, or other characteristics may not suffice to predict physician perception or behavior when caring for patients with cancer …”
Section: Discussionsupporting
confidence: 78%